The magic book as a cooperative learning strategy to develop writing skills amongst eighth-grade students at 27 de febrero high school, 2014 -2015 academicperiod - Valdiviezo Puglla, Leticia Piedad (2016)
This research work had the purpose of determining how the use of the magicbook influenced on the writing skills among eight-grade students at 27 de Febrero high school 2014-2015 academic period. In order to carry out this study, it was necessary the applicat ion of the following methods: scientific, analytic-synthetic, statistic, and descriptive.The instruments selected for this study were the test, questionnaire and observation, which were applied to the population from 27 de Febrero high school. The findings revealed that the magic book as a cooperative learning strategy to develop writing skills is useful to improve the writing skills, for this reason is important that the teachers work in a cooperative way, through of this, students writing skills will improve.